Mothers' knowledge of child health matters: Are we doing enough? - Ibrahim H Al-Ayed (Wolters Kluwer Medknow Publications, 2010)
Background: Child care is mostly the responsibility of mothers. Several studies have revealed that the mothers' education has a positive impact on their knowledge and practice in child health matters. Objectives: The study was undertaken to assess the level of mothers' knowledge on certain aspects of child health care and whether there is any correlation between their level of knowledge and the number of years of formal education they have had. Materials and Methods: A two-part questionnaire was distributed. The first part comprised information about mother's nationality, age, work, level of education and number of children, in addition to sources of health information and the role of school education in child health matters. The second part contained 40 statements about different aspects of child health matters. A structured interview with the mothers who attended with their children at the pediatric outpatient clinic of King Khalid University Hospital in Riyadh during July and August 2007, was conducted by a trained non-medical research assistant using the items and statements of the questionnaire as a base. A knowledge score was calculated from the number of correct answers. The maximum score was 40. An arbitrary cut-off score of 25 was considered satisfactory. Results: Three-hundred-seventy-three questionnaires were completed. The mean score of the total sample was 25 (out of 40) and the minimum score obtained was 14, and the maximum 36. Fifty-eight percent scored 25 or more. Scrutiny of individual items on the questionnaire revealed significant and serious gaps in mother's knowledge. No statistically significant correlation was evident between mothers' knowledge of child health related matters and level of education, age, or number of children. Conclusion: Mothers' knowledge of child health related matters is deficient. At present, knowledge on child health matters taught in schools in the Kingdom is inadequate. Health care institutions play a limited role in health education. There should be proper effective practical means of disseminating information on child health matters among mothers in our community.